Attentional bias in opioid users: A systematic review and meta-analysis. (1st October 2018) - MacLean, R. Ross; Sofuoglu, Mehmet; Brede, Emily; Robinson, Cendrine; Waters, Andrew J.
Highlights: There is a need for treatments adjunctive to Medication Assisted Treatment (MAT). MAT may not reduce cue-induced craving or attentional bias to opioid cues. Meta-analysis reveals robust attentional bias to opioid cues even on MAT. Attentional bias may be an effective treatment target for opioid use disorder (OUD). Abstract: Background: Opioid use in the United States is a national public health emergency. The primary treatment for opioid use disorder (OUD) is medication assisted treatment (MAT). Although effective in improving treatment outcomes in OUD, there is a need to develop behavioral treatments adjunctive to MAT. The current study investigates attentional bias in OUD as a possible target for adjunctive behavioral treatments. Methods: Comprehensive literature searches of psychological, medical, and educational databases were conducted through October 2017. Eligible peer-reviewed studies evaluated attentional bias in opioid users, used a task to evaluate attentional bias that included active response to study stimuli, calculated attention bias by comparing response to drug and neutral stimuli, and could isolate attentional bias specific to opioid versus neutral stimuli from bias to other salient stimuli. Conclusions: The results of our systematic review and meta-analysis suggest that individuals with OUD exhibit robust attentional bias to opioid cues, even when engaged in MAT. Interventions that reduce attentional bias may be a useful adjunct to MAT.